Identidade profissional do psicólogo clinico: transformações no contexto atual - Spinelli, Maria Rosa (2010)
Topic: The Professional Identity of the Clinical Psychologist: changes in the current scenario. Objective: To examine the ongoing changes in the current scenario of clinical psychology practice and how such professional identity is defined. Method: Qualitative and Quantitative Clinical Methods built as from the matching of two dense methodologies: on the one hand, we have used the epistemological concepts of the qualitative methods (description comprehension interpretation) of the research conducted from the perspective of the human sciences and, on the other hand, the quantitative method, which requires the measuring, balancing and study of the data proposed. We have also employed the clinical-psychological knowledge and behavior developed through a psychological focus on interpersonal relations and through the history of such relations in the socio-psycho-physical field. Individuals: The criteria used to include the individuals in this study were the following: a. Be a clinical psychologist with an email address for contact purposes and professional experience between 20 and 47 years; b. Be registered as a clinical psychologist with the CRP-06 [Accreditation Entity] as of 1962 (the year in which the law regulating the profession was created); c. Submit an express consent for his/her participation in the research by signing the Termo de Consentimento Livre e Esclarecido . The group we studied was composed by 236 individuals, indicated by the CRP-06, the sample including 164, who agreed to respond to the research questionnaire previously, by email. Analysis: As an evaluation tool, the techniques chosen to deal with the collected data were the Collective Subject Discourse-DSC (LEFÈVRE and LEFÈVRE, 2005), and the Quantitative Analysis of Data and Qualitative Analysis of Content , which enabled the categorization/sub-categorization of the data based on an examination of the set of questionnaires received. The analysis of the data was carried out in light of the theories of Winnicott, D.W.; Giddens, A.; Taylor, C., and with a psychosomatic approach. Results: We have come to the conclusion that the psychologists included in the sample we have analyzed have a Professional Identity . They are middle-class psychologists who love their work, study constantly, but lack the financial resources that could help them conduct more studies and research and be more dedicated. They have showed their skills, competence and responsiveness. They play an important role in the health area and in society in general, being recognized by their work. They are in the hospitals, private offices and in public services. They are concerned with the challenges of the present, as the pathologies have increased and the time/space relation has been accelerated , the new technologies supply new scientific resources, but, at the same time, they demand new techniques and changes in the therapeutic setting. Subjectivity requires further studies and adaptation to such new social context. The academic courses are not doing a good job in preparing such professionals to work in the present time